2018
DOI: 10.1183/16000617.0045-2018
|View full text |Cite
|
Sign up to set email alerts
|

How long is too long? A scoping review of health system delays in lung cancer

Abstract: Earlier access to lung cancer specialist (LCS) care improves survival, highlighting the need for streamlined patient referral. International guidelines recommend 14-day maximum time intervals from general practitioner (GP) referral to first LCS appointment ("GP-LCS interval"), and diagnosis to treatment ("treatment interval"). We compared time intervals in lung cancer care against timeframe benchmarks, and explored barriers and facilitators to timely care.We conducted a scoping review of literature from MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 58 publications
3
61
1
2
Order By: Relevance
“…Hypofractionated treatments in palliative settings may provide equivalent symptom relief across multiple disease sites [16], while reducing the number of treatment visits and potentially the length of stay, and should be considered in this population when possible. In Start date of palliative radiotherapy addition, although the median of 6 days from the decision to treat date to the start of palliative radiotherapy for our study patients is comparable with the median of 7 days (range 0e123) for all patients with cancer from our province treated with palliative radiotherapy at TOH from 2016 to 2018, the time from biopsy to the start of radiotherapy in our study was about 20 days, with international guidelines again recommending 14 days from diagnosis to treatment for lung cancer patients [14]. Rapid access palliative radiotherapy programmes have been shown to improve access to care, while delivering more timely and efficient treatment in several settings worldwide [17].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hypofractionated treatments in palliative settings may provide equivalent symptom relief across multiple disease sites [16], while reducing the number of treatment visits and potentially the length of stay, and should be considered in this population when possible. In Start date of palliative radiotherapy addition, although the median of 6 days from the decision to treat date to the start of palliative radiotherapy for our study patients is comparable with the median of 7 days (range 0e123) for all patients with cancer from our province treated with palliative radiotherapy at TOH from 2016 to 2018, the time from biopsy to the start of radiotherapy in our study was about 20 days, with international guidelines again recommending 14 days from diagnosis to treatment for lung cancer patients [14]. Rapid access palliative radiotherapy programmes have been shown to improve access to care, while delivering more timely and efficient treatment in several settings worldwide [17].…”
Section: Discussionsupporting
confidence: 74%
“…We felt that this was quite a rapid time interval for patients to be flown to Ottawa once suspected of having a cancer diagnosis, considering the logistical planning required. Indeed, most international guidelines recommend a maximum time interval from referral to specialist appointment of 14 days for lung cancer patients [14], which formed the majority of our study sample. These results are encouraging and speak to the significant coordinated efforts in place to help provide timely access to tertiary care, including radiotherapy, for patients from Nunavut.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recall bias was minimised by the triangulation of different data sources and by patients completing the questionnaire within a limited time window (median 5 months) after the cancer diagnosis. (26) 59 (23) 52 (26) 51 (26) 62 (22) 41 2047 (16) 49 2332 3633 (16) 481 (22) <0.001 ¶ ‡ Poor 20 (9) 11 414 716 (8) 18 64 216 69 46 710 5124 ( 15 611 (6) 17 (9) 15 (5) 21 (10) 55 (19) 48 2314 1624 (12) 231 (11) <0.001 ¶ ‡ Missing 28 (13) 20 813 717 (9) 38 (13) 11 59 34 29 103 1152 7Ethnicity n(%) White Smoking n(%) Never 13 (6) 18 712 (6) 19 (10) 15 (5) 22 1131 1141 (19) 11…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…No symptoms 29 (14) 24 (10) 32 (16) 21 (11) 63 (22) 50 (25) 67 2336 1733 (38) 75 (36) 430 (20) <0.001 45 (39) n/a 67 (44) 24 2818 (30) n/a 7 (41) 33 (41) 284 (39) 0.093 Breathlessness 17 (20) 27 (20) 20 (17) n/a 27 (18) 11 (13) 11 (18) n/a 4 2413 (16) 130 (18) 0.803 Non-specific symptom 11 (13) 23 (17) 19 (17) n/a 39 (26) 7 85 (8) n/a 5 (29) 13 (16) 122 (17) No symptoms/missing 12 (14) 13 (10) 17 (15) n/a 18 (12) 43 5018 (30) n/a 2 12) 20 (25) 143 (19) All figures are n (% Open access survival differences. 38 The rate of respondents who attended A&E varied twofold across jurisdictions from 9%-10% in England, Scotland and Denmark to 18%-20% in Northern Ireland, Ontario and Manitoba.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…An audit of the respiratory service at our hospital several years ago demonstrated that 73% of suspected lung cancer referrals were reviewed within two weeks [10]. However, the most recent scoping review on the topic suggests variability in review times, ranging from 0 to 33 days across 23 countries, compared to the recommended 14 days [11]. The case-mix of a typical respiratory service has not been documented but the high prevalence of lung nodules and their inclusion in suspected lung cancer referral pathways dictates that a meaningful proportion of the workload will be attributable to lung nodules with low malignancy risk.…”
Section: Introductionmentioning
confidence: 99%